Relationship of Gaming Disorder with parenting based on low affection-communication and personality trait of neuroticism in adolescents - Rodríguez-Ruiz, Francesc; Marí-Sanmillán, María Isabel; Benito, Ana; Castellano-García, Francisca; Sánchez-Llorens, Marta; Almodóvar-Fernández, Isabel; Haro, Gonzalo (Frontiers in Psychology, 2023)
Background Gaming Disorder is increasingly common in adolescents. We aimed to evaluate the relationship between parenting, personality traits, and Gaming Disorder. Methods An observational and cross-sectional study in six secondary schools of Castelló, obtaining a final sample of 397 students. Results Adolescents with Gaming Disorder had lower scores in Adolescent Affection-Communication (F = 8.201; p < 0.001), Father’s Warmth (F = 3.459; p = 0.028), and Father’s Acceptance/Involvement (F = 5.467; p = 0.003), and higher scores in Mother’s Revoking Privileges (F = 4.277; p = 0.034) and Father’s Indifference (F = 7.868; p = 0.002) than healthy participants. Male sex was a risk factor for Gaming Disorder (OR = 12.221; p = 0.004), while Adolescent Affection-Communication (OR = 0.908; p = 0.001) and Agreeableness (OR = 0.903; p = 0.022) were protective factors. Data modeling described the protective effect that Adolescent Affection-Communication had on Gaming Disorder, which was both directly (B = -0.20; p < 0.001) and indirectly mediated by Neuroticism (B = -0.20; p < 0.001), while Neuroticism itself was a risk factor for Gaming Disorder (B = 0.50; p < 0.001). Conclusion These results reflect that Parental style with low affection and communication was directly and indirectly related to the Gaming Disorder, as well as male sex and personality trait of Neuroticism.